Sex-Specific Associations Between Inter-Individual Differences in Heart Rate Variability and Inter-Individual Differences in Emotion Regulation - Lischke, Alexander; Weippert, Matthias; Mau-Moeller, Anett; Päschke, Stefanie; Jacksteit, Robert; Hamm, Alfons O.; Pahnke, Rike (Frontiers in Neuroscience, 2019)
Neurobiological theories suggest that inter-individual differences in heart rate variability (HRV) have the potential to serve as a biomarker for inter-individual differences in emotion regulation that are due to inter-individual differences regarding the engagement of prefrontal and (para-)limbic brain regions during emotion processing. To test these theories, we investigated whether inter-individual differences in HRV would be associated with inter-individual differences in emotion regulation. We determined resting state HRV in a sample of 176 individuals that had also completed a short self-report measure of reappraisal and suppression use. HRV was derived from short-term (300 s) and ultra-short-term (120 s, 60 s) recordings of participants’ heart rate to determine the robustness of possible findings. Irrespective of recording length, we found that an increase in HRV was associated with an increase in reappraisal but not suppression use. However, this association was only evident among male but not female participants, indicating a sex-specific association between inter-individual differences in HRV and inter-individual differences in emotion regulation. These findings, which are consistent with previous ones, suggest that inter-individual differences in HRV may indeed work as a biomarker for inter-individual differences in emotion regulation. We, thus, recommend the use of ultra-short-term HRV measures and short self-report measures of emotion regulation strategies for researchers who have to investigate the neurobiological mechanisms of emotion regulation in a time- and resource-efficient manner.